(untitled) (Nordic Journal of African Studies, 2001)
Muslim women are frequently perceived as oppressed and subjugated people with marginal, or even counterproductive, economic role in the society. The paper argues that the Muslim Hausa women in Northern Nigeria, through hidden economic activities in their households, can bypass the open market and contribute significantly to the economic progress of the society. The paper also argues on the basis of the comparison between Muslim and non-Muslim women that Islam does not inhibit economic activities of Muslim Hausa women. Differences between Muslim and non-Muslim women were found. While strictly secluded Muslim women were hardly found in factories, they contributed to the economy by involving themselves in the hidden informal economic sector. (Ed.)